Policy and investment reform case studies - Nehring, Ryan; Ghosh, Ritwick; Sanyang, Sally (CGIAR System Organization, 2025)
These case studies were prepared in coordination with a World Bank report: Rooted: Agriculture Rooted in Biodiversity https://hdl.handle.net/10986/44098. Specific authorship and order may vary. This record includes the following case studies: